(untitled) (International Journal of Engineering and Computer Science, 2018)
with the rapid increase of technology, the data stored and transmitted among the client and server has been increased tremendously. In order to provide high security for the confidential data, there is a need for proper encryption techniques that are to be followed by the concerns. This paper presents an analysis of the various encryption algorithms and their performance on handling the private data with authentication, access control, secure configuration and data encryption. Document oriented databases such as MongoDB, Cassandra, CouchDB, Redis and Hypertable are compared on the basis of their security aspects since they manipulate the huge amount of unstructured data in their databases. It is proposed that each database has its own security breaches and emphasises the need for proper encryption methods to secure the data stored in them.